Influence of Continuous Elbow Valgus Stress on the Medial Elbow Joint Space. Issue 10 (11th October 2021) - Ikuta, Tomoya; Yoshioka, Kanta; Matsuzawa, Kanta; Maruyama, Sae; Edama, Mutsuaki
Background: To investigate the effect of ulnar collateral ligament stretching due to the "creep phenomenon, " the effect of accumulating elbow valgus stress on ligaments must be clarified. Purpose: To evaluate the effect of continuous elbow valgus stress on the medial elbow joint space (JS). Study Design: Controlled laboratory study. Methods: The authors measured the JS of the nondominant elbow joints of 20 healthy male university students (age, 21.4 ± 0.5 years; height, 171.4 ± 6.5 cm; weight, 65.7 ± 9.1 kg). The participants were seated with their shoulder at 90° of abduction and external rotation and their elbow at 30° of flexion, and elbow valgus stress was maintained at loads of 30 and 60 N using a Telos stress device. The JS was measured on ultrasound images of the medial elbow joint with the elbow in the start limb position (0 N) and then immediately (0 seconds) and at 60, 120, 180, 240, and 300 seconds after loading. In addition, muscle activity of the pronator teres muscle during JS measurement was monitored to examine the presence or absence of defensive contraction due to pain. Analysis of variance and the Bonferroni method for post hoc testing were used for statistical analysis. Results: No participants showed defensive contractions of the pronator teres. At 30 N, JS was significantly larger 60 seconds after loading compared with immediately after loading ( P = .007). At 60 N, JS was significantly larger after 120 seconds, as the loading time of valgus stress increased, compared with immediately after loading ( P = .002). Conclusion: JS was significantly larger immediately after loading of valgus stress, with an increase in continuous elbow valgus stress after 60 seconds at 30 N and after 120 seconds at 60 N. These results suggest that a creep phenomenon may develop around the soft tissue of the elbow when loaded by a continuous valgus stress. Clinical Relevance: JS is significantly increased by continuous elbow valgus stress.